Human–animal relations and the celebration of place‐identity: A case study of the Scone Racing Carnival, New South Wales. (10th November 2015) - Graham, Raewyn
Abstract: Festivals and carnivals are social‐cultural assemblages of human and non‐human entities. This paper investigates interactions between humans and animals by focusing on the Scone Racing Carnival, a key event in the Scone and Upper Hunter Horse Festival. This paper contributes to existing studies of non‐metropolitan festivals and animal–human relations by questioning how and why non‐humans are enrolled in these cultural events, and the impact this has on place identity. The central argument is that the relationship between humans and thoroughbred horses, in particular, has played a significant role in the creation of a distinctive landscape, a regional identity for the Upper Hunter region of New South Wales, and a local identity for Scone. In turn, the carnival has assisted in maintaining an 'eque‐cultural' identity through the marketing and annual public celebration of human–horse relationships.